Learning from host-defense peptides: cationic, amphipathic peptoids with potent anticancer activity. - Wei Huang; Jiwon Seo; Stephen B Willingham; Ann M Czyzewski; Mark L Gonzalgo; Irving L Weissman; Annelise E Barron (PLoS ONE, 2014)
Cationic, amphipathic host defense peptides represent a promising group of agents to be developed for anticancer applications. Poly-N-substituted glycines, or peptoids, are a class of biostable, peptidomimetic scaffold that can display a great diversity of side chains in highly tunable sequences via facile solid-phase synthesis. Herein, we present a library of anti-proliferative peptoids that mimics the cationic, amphipathic structural feature of the host defense peptides and explore the relationships between the structure, anticancer activity and selectivity of these peptoids. Several peptoids are found to be potent against a broad range of cancer cell lines at low-micromolar concentrations including cancer cells with multidrug resistance (MDR), causing cytotoxicity in a concentration-dependent manner. They can penetrate into cells, but their cytotoxicity primarily involves plasma membrane perturbations. Furthermore, peptoid 1, the most potent peptoid synthesized, significantly inhibited tumor growth in a human breast cancer xenotransplantation model without any noticeable acute adverse effects in mice. Taken together, our work provided important structural information for designing host defense peptides or their mimics for anticancer applications. Several cationic, amphipathic peptoids are very attractive for further development due to their high solubility, stability against protease degradation, their broad, potent cytotoxicity against cancer cells and their ability to overcome multidrug resistance.